2019
DOI: 10.1111/aphw.12176
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Habit in Self‐Reported and Observed Hand Hygiene Behavior

Abstract: Background The present contribution tests the main ideas that (a) hand hygiene behavior is associated with habit, and (b) this association is robust when deliberative constructs (i.e. knowledge and intention) are controlled for, indicating an automatic component in hand hygiene behavior. Methods Two correlational studies using different operationalisations of hand hygiene behavior are reported. In Study 1, hand hygiene was assessed in the context of food preparation; data were measured using the Day Reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
(99 reference statements)
0
16
0
3
Order By: Relevance
“…Research indicates that hand hygiene behaviour is defined at an early stage through role models such as parents or guardians which will influence their practice until changed through education. The results of the study may indicate a link between the reported lack of early parental influence, particularly in UK respondents, and the subsequent lack of knowledge and poor practice of good hand hygiene compliance which then persists until corrected [ 31 , 32 , 33 , 34 , 35 ]. Hand hygiene education targeted at parents may have the potential to make significant improvements in hand hygiene performance for present and future generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that hand hygiene behaviour is defined at an early stage through role models such as parents or guardians which will influence their practice until changed through education. The results of the study may indicate a link between the reported lack of early parental influence, particularly in UK respondents, and the subsequent lack of knowledge and poor practice of good hand hygiene compliance which then persists until corrected [ 31 , 32 , 33 , 34 , 35 ]. Hand hygiene education targeted at parents may have the potential to make significant improvements in hand hygiene performance for present and future generations.…”
Section: Discussionmentioning
confidence: 99%
“…Most hand hygiene behaviour is thought to be inherent in nature and is typically defined at an early age through a mixture of early childhood education on personal hygiene and through the influence of key role models like parents and teachers in reinforcing the behaviour [ 31 , 32 , 33 , 34 ]. Therefore, if hand hygiene education at an early age is inadequate, or influence from key role models is inaccurate, then poor behaviour will persist unless otherwise corrected [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…HH behaviours are complex and multifactorial. Behavioural determinants consist of both deliberative and automatic influences [32], such as psychological, social, emotional, environmental, and habitual factors [33,34]. An individual's propensity to engage in effective HH behaviours is likely to depend on a variety of these factors, and different individuals in a population group are also likely to depend on differing factors [35].…”
Section: Introductionmentioning
confidence: 99%
“…All the 89 reviewed studies were published between 2009 and 2020, with 9 (10%) dated in or before 2010 [ 42 , 46 , 56 , 60 , 81 , 83 , 86 , 92 , 113 ], 38 (43%) dated between 2011 and 2015 [ 32 , 33 , 36 , 38 , 39 , 45 , 48 , 49 , 51 , 52 , 54 , 59 , 61 , 63 - 65 , 67 , 68 , 72 , 73 , 78 - 80 , 82 , 84 , 87 - 89 , 93 - 97 , 99 - 101 , 108 , 116 ], and 42 (47%) dated in or after 2016 [ 25 , 29 - 31 , 34 , 35 , 37 , 40 , 41 , 43 , 44 , 47 , 50 , 53 , 55 , 57 , 58 , 62 , 66 , 69 - 71 , 74 - 77 , 85 , 90 , 91 , 98 , 102 -…”
Section: Resultsmentioning
confidence: 99%